Irisin preserves mitochondrial integrity and function in tubular epithelial cells after ischemia–reperfusion‐induced acute kidney injury - Cui, Yu; Yu, Lu; Cong, Wenqi; Jiang, Shan; Qiu, Xingyu; Wei, Chunchun; Zheng, Gui; Mao, Jianhua; Liu, Ruisheng; Patzak, Andreas; Persson, Pontus B.; Chen, Jianghua; et al. (Acta Physiologica, 2024)
Aims A myokine secreted by skeletal muscles during exercise called irisin mitigates ischemia–reperfusion (I/R) injury in epithelial cells of various organs by limiting damage to mitochondria. We test whether irisin may preserve the mitochondrial integrity and function in renal tubular epithelial cells and protect against ischemia–reperfusion‐induced acute kidney injury (AKI). Methods We correlated serum irisin levels with serum creatinine and BUN levels from both AKI patients and healthy individuals. In mice with irisin administration, various renal injury markers such as serum creatinine, BUN, kidney injury molecule‐1 (Kim‐1), and neutrophil gelatinase‐associated lipocalin (NGAL), and renal histopathology were assessed after I/R. To identify the potential mechanisms of the protective of irisin's protective effect, we perfused proximal tubules under confocal microscopy and analyzed kidney tissues by qPCR, western blot, and immunohistochemistry. Results Serum irisin correlated inversely with serum creatinine and BUN levels were significantly lower in AKI patients than in healthy subjects. Administering irisin to mice after I/R decreased biomarker levels for AKI including serum creatinine, BUN, Kim‐1, NAGL and lessened histological changes. In kidney tissues of mice, irisin upregulated the mitochondrial autophagy marker protein microtubule‐associated protein 1 light chain 3 (LC3), the mitochondrial autophagy pathway‐related proteins PTEN‐induced putative kinase 1 (PINK1) and Parkinson's disease 2 parkin (PARK2) and downregulated the reactive substrate protein sequestosome 1 (P62) and mitochondrial membrane proteins translocase of outer mitochondrial membrane 20 (TOM20) and translocase of inner mitochondrial membrane 23 (TIM23). Conclusion Irisin protects against renal I/R injury, which may involve the preservation of mitochondrial integrity and function.